The role of short-chain fatty acid in metabolic syndrome and its complications: focusing on immunity and inflammation - Yu, Wenqian; Sun, Siyuan; Yan, Yutong; Zhou, Hong; Liu, Ziyi; Fu, Qiang (Frontiers in Immunology, 2025)
Metabolic syndrome (Mets) is an important contributor to morbidity and mortality in cardiovascular, liver, neurological, and reproductive diseases. Short-chain fatty acid (SCFA), an organismal energy donor, has recently been demonstrated in an increasing number of studies to be an important molecule in ameliorating immuno-inflammation, an important causative factor of Mets, and to improve lipid distribution, blood glucose, and body weight levels in animal models of Mets. This study reviews recent research advances on SCFA in Mets from an immune-inflammatory perspective, including complications dominated by chronic inflammation, as well as the fact that these findings also contribute to the understanding of the specific mechanisms by which gut flora metabolites contribute to metabolic processes in humans. This review proposes an emerging role for SCFA in the inflammatory Mets, followed by the identification of major ambiguities to further understand the anti-inflammatory potential of this substance in Mets. In addition, this study proposes novel strategies to modulate SCFA for the treatment of Mets that may help to mitigate the prognosis of Mets and its complications.